Interference cancellation through interference forwarding in relay-assisted systems - Sirigina, Rajendra Prasad (2020)
Interference forwarding and multiuser (MU) codes are potential solutions to manage moderate interference. In particular, MU codes based simplified Han-Kobayashi (SHK) scheme is known to achieve sum-rate within one bit of outer bound for a two-user interference channel. However, if each user has its own quality-of-service requirements, it is unknown whether the SHK scheme performs better compared to that of single-user (SU) codes. We investigate whether the SHK scheme with full-duplex decode-and-forward relay can achieve better diversity gain than SU codes for altruistic and selfish modes. In the altruistic mode, the interfering transmitter lets the interference-limited receiver operate at the interference-free diversity order, and in selfish mode, the interfering transmitter optimizes its receiver's diversity order. In both modes, the SHK scheme is shown to provide better diversity gain region (DGR) than the SU codes based transmission scheme only if the interference is weak and the multiplexing gain of the interference is high. Moreover, if the self-interference is not eliminated, relay based SHK protocol cannot operate in selfish mode and also, the multiplexing gain region where the relay based SHK scheme achieves better DGR than other schemes reduces.